Gabapentin versus Midazolam as premedication for anxiolytics in Total Abdominal Hysterectomies - Saghir, Rubab; Khaleeq, Sadia; Rehman, Abdul; Riaz, Ammara (Indus Journal of Bioscience Research, 2025)
Background and Objectives: The uterus can frequently be surgically eliminated through an abdominal incision in an abdominal hysterectomy. During the process, pre-operative anxiety in patients in response to unfavorable conditions can lead to physiological changes such as heart arrhythmias, tachycardia, and hypertension, which can impact patient's surgery experience and result in adverse effects and a brief hospital stay following surgery. Therefore, it is fundamental to reduce a patient's anxiety by performing a thorough pre-anesthetic treatment. The present study aimed at elucidating the comparison between Gabapentin and Midazolam in reducing pre-operative anxiety in patients undergoing abdominal hysterectomy. Material and methods: A double-blinded a controlled trial occurred at the Department of Anesthesia, Services Hospital Lahore. 52 cases entirety, divided into two groups (G group and M group) with 26 treatments each. Non-probability, sequential sampling was the method used. Results: According to the study's findings, the Midazolam group's mean systolic and diastolic blood pressures were considerably lower than those of the Gabapentin group. Similarly, the Gabapentin group's mean heart rates were 98.30 ± 14.09 bpm, whereas the Midazolam group's was 83.55 ± 8.08 bpm.The mean respiratory rate was slightly higher in the Midazolam group (18.55 ± 15.22 breaths/min) compared to the Gabapentin group (16.15 ± 2.46 breaths/min), but this difference was not statistically significant (t = 0.696, p = 0.491). The mean Hamilton Anxiety Scoring Time was significantly lower in the Midazolam group (4.85 ± 0.88 min) compared to the Gabapentin group (7.45 ± 2.69 min). The study has indicated that both drugs significantly reduced Hamilton Anxiety scores, indicating effective anxiolytic properties. Conclusions: Gabapentin group had a higher as well as inconsistent anxiety reduction while Midazolam showed comparatively reliable anxiolytic effects.